2017
DOI: 10.1002/msc.1193
|View full text |Cite
|
Sign up to set email alerts
|

Progressive resistance training (PRT) improves rheumatoid arthritis outcomes: A district general hospital (DGH) model

Abstract: Patients with early and established inflammatory arthritis alike benefited from a 6-week PRT programme provided within a National Health Service setting. Although further work is needed to look at long-term effects, we suggest that this intervention should be more widely available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Resistance training is known as a treatment for muscle mass increase and improves BC. Morsley et al . reported that BF% in 83 patients with RA and other inflammatory arthritis decreased by 1.78 ± 8.22% and HAQ‐DI decreased by 0.24 ± 0.62 (both P < 0.0001) after 6‐week progressive resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance training is known as a treatment for muscle mass increase and improves BC. Morsley et al . reported that BF% in 83 patients with RA and other inflammatory arthritis decreased by 1.78 ± 8.22% and HAQ‐DI decreased by 0.24 ± 0.62 (both P < 0.0001) after 6‐week progressive resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be asserted that sexual activity through physical training leads to better physical performance. It has been shown that physical training has many positive effects in patients with RA [ 29 ]. This could also contribute to the explanation of why physical performance is associated with sexual health in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are several implications of the findings for clinical routine that should be stressed: first, we cannot prove that improving physical fitness in RA patients will also improve sexual function and sexual satisfaction. However, several studies have shown the beneficial effects of physical training in RA patients [ 29 , 37 ], and physical training should, therefore, be implemented in RA patients for many different reasons. In addition, the effect of physical training on chronic inflammation has been shown in several studies [ 38 , 39 ], and this could, in addition to many other benefits, also improve sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…Es liegen inzwischen mehrere Studien vor, die einen positiven Effekt von intensiven Krafttraining gerade bei Rheumapatienten unter DMARD-Therapie nachgewiesen haben [1,[13][14][15]. Interessant erscheinen hier insbesondere 2 Studien aus den Niederlanden über "High Intensity Training" mit intensivem Zirkel-Krafttraining zum Muskelaufbau im Vergleich zu einer Kontroll-Gruppe mit "normaler" Physiotherapie".…”
Section: Auswahl Der Sportart Und Studienlageunclassified